IDENTIFYING THE GROWTH OPPORTUNITIES USING PESTLE AND SWOT ANALYSIS APPROACH - Nugraha, Adilah Putri; Khalid , Zulvia (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
As a business company, Heinz Golden Circle, Australia, needs to grow in this challenging business environment. Therefore, identifying the growth opportunity is necessary to be conducted. This paper is aimed at identifying the growth opportunities through the integration of PESTLE and SWOT analyses. PESTLE analysis is used to examine the external environment of the business which include Political, economical, social, technical, legal, and environmental aspects. The SWOT analysis is used to examine both internal and external business environment which consists of Strengths, Weaknesses, Opportunities and Threats.By combining these analyses, this study ofers resilient methods for identifyingbthe potential growth opportunities. The findings suggest that leveraging PESTLE and SWOT analyses not only enrich strategic planning process but also provide detailed perspective to capitalize in emerging opportunities.